2008
DOI: 10.1111/j.1464-5491.2008.02491.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resolution of diabetic macular oedema after discontinuation of thiazolidenediones

Abstract: To the best of our knowledge, this is the first case to document spontaneous resolution of CSMO and improvement in VA on discontinuation of a glitazone. Glitazones have a definitive role in the management of diabetic patients and ophthalmologists and physicians should both be aware that there may be an association with weight gain, peripheral oedema and CSMO. We recommend that ophthalmologists consider discontinuing glitazones in consultation with the diabetologist before embarking on interventional management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
0
17
0
1
Order By: Relevance
“…Rosiglitazone had its marketing authorisation suspended during the study in September 2010 by the European Medicines Agency because of concerns regarding an increased cardiovascular risk. Oedema is a known risk factor when using glitazones and studies have suggested they are associated with an increased risk of MO, [34][35][36] although another study found no association. 37 The recording of the use of glitazones was added to the study protocol in June 2009 because of the uncertainty surrounding their role in the development of MO.…”
Section: Other Recorded Patient Informationmentioning
confidence: 98%
“…Rosiglitazone had its marketing authorisation suspended during the study in September 2010 by the European Medicines Agency because of concerns regarding an increased cardiovascular risk. Oedema is a known risk factor when using glitazones and studies have suggested they are associated with an increased risk of MO, [34][35][36] although another study found no association. 37 The recording of the use of glitazones was added to the study protocol in June 2009 because of the uncertainty surrounding their role in the development of MO.…”
Section: Other Recorded Patient Informationmentioning
confidence: 98%
“…31 Treatment with thiazolidinediones, a class of antihyperglycaemic agents known to cause fluid retention, may be associated with DME, 32 and their discontinuation was reported to result in DME regression. 33 Although this association is unconfirmed, 34 discontinuation of thiazolidinediones in patients with DME is currently recommended. Surgery should be considered in patients with DME owing to a significant epiretinal membrane or demonstrated vitreomacular traction.…”
mentioning
confidence: 99%
“…Although there have been case reports, 26 and retrospective studies [27][28][29][30] in the literature suggesting the association of macular edema with use of a TZD, the overall evidence either proving or disproving it is fair at best. However, most experts in the field believe that TZDs probably exacerbate macular edema and that with discontinuation of TZDs, macular edema may decrease or abate completely.…”
Section: Macular Edemamentioning
confidence: 99%